Determinación de la duración e intensidad de la latencia en semillas de arroz - Arregocés, Oscar (1978)
Germination studies with 11 rice varieties (Oryza sativa L.) indicate that there are significant differences in the duration and intensity of dormancy of this varieties. Removal of the hull increases germination of seed with long and medium dormancies. The treatment with heat (4 days 50C) is a good way to break the long or medium seed dormancies and weak intensity. There is no relation between the duration and the intensity of dormancy